Enhancing user performance and engagement through gamification: Case study of aqua republica - Pradorn Sureephong (2018)
© 2016 IEEE. Implementing game-elements could be beneficial for both participant motivation and performance or outcome. Thus, several researches have argued that the value of gamification could come at a cost to experience or reliability of the task. However, there are only a few studies focusing on game elements and their effect on user performance. In our research, in a set of studies we examined the effects of cooperation, leader boards and awarding badges-basic elements of gamification-by the application of a serious game called Aqua Republica, developed in collaboration with the UNEP-DHI Centre. The experiment design was based on a performance comparison between a 'Gamified' group and a 'Non-Gamified' group playing Aqua Republica with different gamification environment settings. The indicators of the experiments directly measured the actual use in terms of numerical indicators and self-report. In addition, we have found that using leveling and achievement for the 'Gamified' group resulted in a slightly higher performance compared to the 'Non-Gamified' group. The overall performance was higher throughout the whole session in the 'Gamified' group.